Impacts of Design Parameters on the Thermal Performance of a Macro-Encapsulated Phase-Change-Material Blind Integrated in a Double-Skin Façade System - Yilin Li; Wenshan He; Wanting Tao; Caiyi Yang; Yidong Li; Jo Darkwa (Energies, 2025)
Double-skin façades (DSFs) are promising sustainable design elements of buildings. However, they are prone to overheating problems in warm seasons due to high outdoor temperatures and intense solar radiation. Although phase-change material (PCM) blinds have proved to be effective at enhancing the thermal performance of DSFs, the impacts of the design parameters are crucial to the overall thermal performance of the system. This study focused on analyzing the impacts of design parameters on the thermal performance of a ventilated DSF system, which consisted of a macro-encapsulated phase-change material (PCM) blind with an aluminum shell. A simulation study was conducted using ANSYS Workbench FLUENT software, and the temperature distributions of the integrated system were compared with different blind tilt angles and ratios of cavity depth to blind width. The results show that both the blind tilt angle and ratio of cavity depth to blind width had a significant influence on the thermal performance of the DSF system. For instance, lower air-cavity temperatures within the range of 37~40 °C were achieved with the PCM blind at tilt angles of 30° and 60° compared with other selected tilt angles (0° and 90°). In terms of the cavity depth to blind width ratio, a ratio of 2.5 resulted in a lower air-cavity temperature and a better thermal performance by the DSF. With the optimal blind tilt angle and cavity depth to blind width ratio, the integrated DSF and macro-encapsulated PCM-blind system can reduce the cavity temperature by as much as 2.9 °C during the warm season.